2019
DOI: 10.1136/neurintsurg-2019-015336
|View full text |Cite
|
Sign up to set email alerts
|

Volume variation may be a relevant metric in the study of aneurysm pulsatility: a study using ECG-gated 4D-CTA (PULSAN)

Abstract: ​Background and purposeIntracranial aneurysms are a frequently occurring disease, with an estimated prevalence of 2–5% in the general population. They usually remain silent until rupture occurs, with a mortality rate of 35–50% and a high rate of morbidity, including long-term disability. However, preventative treatments have their own risk of complications and morbi-mortality rates, including stroke and hemorrhage. ECG-gated four-dimensional CT angiography (4D-CTA) allows the acquisition of time-resolved three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Unlike 3D-CTA, 4D-CTA can acquire time-resolved three-dimensional reconstructions to provides dynamic information on aneurysm wall and visualizes wall motion during cardiac cycle. Therefore, irregular pulsation detected by 4D-CTA could be a novel imaging marker of aneurysm vulnerability [ 12 ]. The objective of this proof-of-concept study is to investigate the association of the morphological risk factors characterized by 4D-CTA and DSA.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike 3D-CTA, 4D-CTA can acquire time-resolved three-dimensional reconstructions to provides dynamic information on aneurysm wall and visualizes wall motion during cardiac cycle. Therefore, irregular pulsation detected by 4D-CTA could be a novel imaging marker of aneurysm vulnerability [ 12 ]. The objective of this proof-of-concept study is to investigate the association of the morphological risk factors characterized by 4D-CTA and DSA.…”
Section: Introductionmentioning
confidence: 99%
“…When comparing our study to the literature on cerebral arteries, one other clinical study assessed the reproducibility between multiple pulsation cycles for intracranial aneurysms. [13] This study showed high reproducibility in measuring the maximum volume change per cardiac cycle, for aneurysms exceeding 5 mm, with variations of approximately 0.5 mm. It is essential to note that our study differs in scope as we comprehensively assessed the entire pulsation pattern, unlike this previous study which focused on the maximum volume change measurement.…”
Section: Discussionmentioning
confidence: 62%
“…Although no significant difference existed between unruptured aneurysms and normal intracranial arteries, there was still a slight distinction ( 21 ). 4D-CTA is a feasible method for quantitatively analyzing the volume changes of aneurysms during a cardiac cycle, providing a theoretical basis for further research ( 22 , 23 ). In this study, the comparison between ruptured and unruptured aneurysms revealed a significant difference in volume change rate between the two groups.…”
Section: Discussionmentioning
confidence: 99%